Imidazolium Based Ionic Liquids: A Promising Green Solvent for Water Hyacinth Biomass Deconstruction - Singh, Jitendra Kumar; Sharma, Rahul Kumar; Ghosh, Pushpal; Kumar, Ashwani; Khan, Mohammed Latif (Frontiers in Chemistry, 2018)
Water hyacinth (WH) is a troublesome aquatic weed of natural and artificial water bodies of India and other tropical countries and causing severe ecological problems. The WH biomass is low in lignin content and contains high amount of cellulose and hemicellulose, making it suitable material for conversion into liquid fuels for energy production. This study highlighted that, how different imidazolium based ionic liquids (ILs) [1-alkyl-3-methylimidazolium bromide, [Cnmim]Br (n = 2, 4, 6, 8, and 10)] with tunable properties can be employed for the degradation of WH biomass. Different characterizations techniques such as XRD, FT-IR, SEM and DSC are used to unravel the interplay between ILs and the biomass. In this study, it is observed that [Emim][Br] pretreated samples have maximum crystalline value (Crl = 26.38%) as compared to other ionic liquids pretreatments. FTIR data showed the removal of lignin from WH biomass by 12.77% for [Emim][Br] and 10.74% for [Edmim][Br]. SEM images have proven that [Emim][Br] pretreatment have altered the structure of biomass the most. Our results proved that IL pretreatment is a promising approach for effective treatment of WH biomass and causes high levels disruption of cellulose structure.